Analisis Nilai Return E-IPO yang Terdaftar di Bursa Efek Indonesia - Eliza, Rispa; T, Jessica; RZ, Rully Setiawan (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2024)
When investing, investors naturally expect returns on the funds they've invested. Therefore, investors need to calculate the returns of the stock companies they invest in. The purpose of this research is to determine the initial opening return value and the initial closing return value of E-IPO companies listed on the IDX for the period of January to April 2023. The analysis method used is quantitative description. The population in this study consists of 34 E-IPO companies from various sectors listed on the IDX during January to April 2023. Data analysis sources are from the Stockbit application, which is registered with the Financial Services Authority (OJK). Based on the research analysis results, the stock company codes LAJU, SAGE, and AWAN have the highest initial opening return values at 35%. Meanwhile, the stock company code CUAN has the highest closing return value at 6002.3%. The return value of each stock company code varies in percentage, influenced by different IPO prices, opening prices, and closing prices for each company. If the IPO price, opening price, and closing price are high, the return value of the stock obtained is also high, and vice versa.